Vascular diseases await translation of blood vessels engineered from stem cells - Samuel, Rekha (Sci Transl Med, 2015)
The discovery of human induced pluripotent stem cells (hiPSCs) might pave the way toward a long-sought solution for obtaining sufficient numbers of autologous cells for tissue engineering. Several methods exist for generating endothelial cells or perivascular cells from hiPSCs in vitro for use in the building of vascular tissue. We discuss current developments in the generation of vascular progenitor cells from hiPSCs and the assessment of their functional capacity in vivo, opportunities and challenges for the clinical translation of engineered vascular tissue, and modeling of vascular diseases using hiPSC-derived vascular progenitor cells.